Febrile coma and disseminated intravascular coagulation following heat stroke. - Lélis, M; do Carmo, G; Caldeira, L; Abreu, J; Freitas, L; Doroana, M (Acta Médica Portuguesa, 1992)
A clinical case that occurred in a 42 years old female and which fulfils the diagnostic criteria for the entity described as Heat Stroke is presented. In this case, besides the usual manifestations of hyperpyrexia without sweating along with consciousness disorders, features of consumptive coagulopathy, rhabdomyolysis and well marked laboratory liver dysfunction have also been found. The severity of this situation and its less common occurrence in temperate climates, together with the uncertainty in establishing the diagnosis, namely when infection is suspected--in the present case the initial diagnosis was Sepsis, which led to patient's admission in an infectious diseases intensive care unit--motivate the authors to make this report. Furthermore, they consider this case to be a good example of the varied clinical and laboratory manifestations and possible severe complications that Heat Stroke may display.